1997
DOI: 10.1097/00000478-199711000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Florid Angiogenesis in Mucosa Surrounding an Ileal Carcinoid Tumor Expressing Transforming Growth Factor-α

Abstract: Carcinoid tumors of the gastrointestinal tract are known to be associated with fibrosis and vascular elastosis, either within the tumor or at distant sites. The current report describes prominent vascular proliferation in the villi extending 38 cm proximal and 15 cm distal to an ileal carcinoid tumor. These villi were expanded by vessels, producing a segmental carpet of multiple small polypoid protrusions around the tumor. Immunohistochemical analysis suggested that the major stromal components were of endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This observation supports the hypothesis that the cell type responsible for small intestinal carcinoids has the highest propensity for the production of growth factors 45 , . 46 …”
Section: Small Intestinementioning
confidence: 99%
“…This observation supports the hypothesis that the cell type responsible for small intestinal carcinoids has the highest propensity for the production of growth factors 45 , . 46 …”
Section: Small Intestinementioning
confidence: 99%
“…This could be due either to: (1) a direct chemotactic effect of TGF-α; (2) interaction of TGF-α with other growth factors or adhesion molecules; (3) a possible role of TGF-α in the induction of angiogenesis within the tumour, as previously suggested (Schreiber et al, 1986;Cai et al, 1997); (4) concomitant autocrine controlled proliferation and protection from apoptosis (Foster et al, 1999). Interestingly, in adenocarcinomas of the distal oesophagus, Sauter et al (1995) have shown that persistent or increased expression of TGF-α after neo-adjuvant therapy is related to poor prognosis.…”
Section: Discussionmentioning
confidence: 93%
“…Anthony and Drury (1970) observed abnormal accumulations of elastin fibres within the intima of mesenteric blood vessels in association with small intestinal carcinoid tumours at distant sites leading to ischaemic necrosis and infarction. Cai and others (1997) observed the production of an angiogenic factor (growth factor α) by neuroendocrine cells, which leads to vascular proliferation (both locally and at distal sites), again potentially leading to gastrointestinal bleeding (McCluggage and others 1999). Finally, circulating vasoactive compounds, such as histamine in dogs (Clemencon and Lawson 1984) and serotonin in man (Ozdemir and others 1972), have been reported as potential inducers of gastric ulceration.…”
Section: Discussionmentioning
confidence: 99%